Making Space in Geographical Analysis. Issue 2 (23rd March 2022) - Franklin, Rachel S.; Delmelle, Elizabeth C.; Andris, Clio; Cheng, Tao; Dodge, Somayeh; Franklin, Janet; Heppenstall, Alison; Kwan, Mei‐Po; Li, WenWen; McLafferty, Sara; Miller, Jennifer A.; Munroe, Darla K.; et al.
Abstract : In this commentary we reflect on the potential and power of geographical analysis, as a set of methods, theoretical approaches, and perspectives, to increase our understanding of how space and place matter for all . We emphasize key aspects of the field, including accessibility, urban change, and spatial interaction and behavior, providing a high‐level research agenda that indicates a variety of gaps and routes for future research that will not only lead to more equitable and aware solutions to local and global challenges, but also innovative and novel research methods, concepts, and data. We close with a set of representation and inclusion challenges to our discipline, researchers, and publication outlets.